ANALISIS FAKTOR PRESTASI BELAJAR PADA MAHASISWA MENINGKAT - Sylvania Arsa Nurhaliza; Christian Wiradendi Wolor; Marsofiyati (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
One aspect of development in education is quality improvement in the implementation of learning because it has a very important and central role in terms of realizing continuous quality improvement. In this case, the quality of education is currently measured using learning achievement as a benchmark in terms of the success of the educational process. This study aims to determine the Influence of Learning Motivation, Self-Regulated Learning, Procrastination, and Self-Efficacy on Learning Achievement in Students. The writing of this study used quantitative methods by collecting data through the distribution of online questionnaires measured using a Likert scale of one to five, as well as the number of samples of 100 respondents with active student criteria in all universities in Indonesia. The sampling technique uses simple random sampling. The data analysis techniques used in this study are path analysis using the SmartPLS 4.0 application. Based on the calculation results, the results of this study show that: (1) learning motivation variables affect learning achievement; (2) self-regulated learning variables affect academic achievement; (3) procrastination variables affect learning achievement; (4) self-efficacy variables affect learning achievement; (5) variables of learning motivation, self-regulated learning, procrastination, and self-efficacy affect learning achievement.